A COMPARATIVE REVIEW OF HUMAN AND VETERINARY GENERIC DRUG APPROVAL SYSTEMS - KARTHIKESAVAN PONMURUGESAN,; VIVEK REDDY MURTHANNAGARI,; HEMALATHA DEVARAJ,; JESWANTH RAJ NAGARAJAN,; GANESH GNK, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
This review compares human and veterinary generics' regulatory regimes with respect to applicable similarities and differences between approval processes, dossier presentation, bioequivalence test protocols, and post-marketing control. Therapeutic equivalence is the aim of both industries, albeit under regulatory regime, there are enormous disparities in bioequivalence protocols, pharmacovigilance schemes, and ethical requirements. These differences lead to inefficiencies, cost increase in drug development, and potential negative effect on animal and human health, specifically AMR and off-labeling. Global issues of new nature, including implications on AMR, controversy of data exclusivity, and animal welfare in clinical trials, are highlighted by the review. Efforts at harmonizing endeavors, for instance, via ICH and VICH are framed as filling the regulation gap. They urge an international concerted effort to align intellectual property rights with the interests of public health and animal welfare and with prudent use of antimicrobials in addition to promoting the One Health approach.